THE TRIUMPHS OF AFFECTIONS: CRÉBILLON FILS, TRANSLATION AND THE EIGHTEENTH-CENTURY ENGLISH NARRATIVES OF MOTION AND EMOTION - BUTOESCU, Elena (Studia Universitatis Babeș-Bolyai Philologia, 2023)
The Triumphs of Affections: Crébillon Fils, Translation and the Eighteenth-Century English Narratives of Motion and Emotion. The French influence on eighteenth-century English sentimental writing has been a rich topic for criticism ever since translations of French novels were imported into England as early as the first decades of the eighteenth century. In the “long” eighteenth-century history of English literature, there was a great deal of translation from French sources, which clearly indicates a market for fiction and the need to satisfy it (sources françaises were often mentioned as tokens of legitimacy). French sources took a stance on English realist fiction by infusing it with emotional narratives of men of feeling that hinged on acts of translation, whereby translation is understood not only as adaptation, but also as resistance against long-standing literary practices that advocated institutionalised moral codes in realistic fiction. Hence, the concerns of this study are threefold: to discuss the ambivalent nature that early modern philosophers granted to emotions, which triggered conflicting motions in an individual or in a specific social context, resulting in a taxonomy of passions; to consider Crébillon fils’s novel in English translation in order to epitomize the new type of discourse that intended to popularize virtue through eroticism, satire and decadence; and to re-ground human experience as it was discussed in eighteenth-century literary texts from the perspective of natural philosophy. This article aims to rethink eighteenth-century affective theory in relation to translation studies, while reading Thomas Hobbes’ concept of motion as a metaphor for the historical and mindset transformations that were fundamental to the writing of the history of literature. REZUMAT. Triumful emoțiilor: Romanul lui Crébillon Fils în contextul traducerilor și al narațiunilor care pun sentimentele în mișcare. Influența narațiunilor franceze asupra romanului sentimental englez din secolul al XVIII-lea a reprezentat un subiect stufos pentru critica literară din momentul în care traducerile din limba franceză au fost adoptate în Anglia în primele decenii ale secolului al XVIII-lea. În istoria literaturii engleze, traducerile din franceză erau ceva obișnuit, dat fiind că modelul cultural francez era dominant, așadar, legitim. Sursele franceze au influențat romanul realist englez prin traducerea prozei sentimentale, actul de traducere reprezentând nu doar adaptarea unui text într-o altă limbă, ci și împotrivirea față de practicile literare ieșite din uz, care propagau principiile codului etico-moral în romanul realist. Astfel, studiul de față își propune trei obiective: să discute caracterul ambivalent pe care filozofii modernității timpurii îl acordau emoțiilor, ceea ce a declanșat o dinamică interioară și socială și a dus la crearea unei taxonomii a pasiunilor; să analizeze traducerea în limba engleză a textului lui Claude Prosper Jolyot de Crébillon pentru a surprinde noul tip de discurs, care viza afirmarea virtuților prin intermediul expozeurilor erotice, satirice și decadente; și, nu în ultimul rând, să redefinească din perspectiva filosofiei naturale experiența umană descrisă în textele literare. Articolul regândește teoria afectelor în relație cu traducerile din secolul al XVIII-lea englez, expunând conceptul dinamic al mișcării al lui Thomas Hobbes ca pe o metaforă a transformărilor istorice și mentalitare, fundamentale pentru evoluția istoriei literaturii engleze. Cuvinte-cheie: traducere, surse franceze, roman sentimentalist, Crébillon fils, dinamică și mișcare, teoria afectelor în secolul al XVIII-lea. Article history: Received 8 July 2023; Revised 7 September 2023; Accepted 12 September 2023; Available online 30 September 2023; Available print 30 September 2023